Prosedur Pelayanan Tiket Pesawat Domestik Garuda Indonesia Di Pt. Dymens Travel Bureau - Elisa Dwi Rohani; Reza Destiani (Jurnal Pariwisata Terapan, 2017)
Garuda Indonesia as national airlines in Indonesia have integrated reservation system. PT. Dymens Travel Bureau, as travel agent which provides Garuda Indonesia’s ticket sales as their main product, implemented this system. This reservation system have some steps that must be done correctly. Besides the system itself, agent must provide equipment such as computers with stable internet connection, staff with high computer and airlines sytem literacy. The aim of this paper is to analyse Garuda Indonesia’s online system ticket reservation at PT. Dymens Travel Bureau. Reservation system is complex thus need higher competency in system literacy to operates it. This research used descriptive qualitative method to exlpain steps of reservation in Garuda Indonesia’s System. This system generates Passenger Name Record (PNR) with passenger information inculidng name, flight schedule, route, class of flight, ticket number, time limit, and booking code. This reseach aslo found some non technical problem in reservation system due lack of competency of staff and unstable internet connection.